2021
DOI: 10.1007/s10291-021-01104-3
|View full text |Cite|
|
Sign up to set email alerts
|

Monitoring and prediction of hurricane tracks using GPS tropospheric products

Abstract: We have reconstructed integrated water vapor (IWV) using the zenith wet delays to track the properties of hurricanes and explore their spatial and temporal distributions estimated from 922 GPS stations. Our results show that a surge in GPS-derived IWV occurred at least six hours prior to the landfall of two major hurricanes (Harvey and Irma) that struck the Gulf and East Coasts of the USA in 2017. We observed enhanced IWV, in particular, for the two hurricanes landfall locations. The observed variations exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Various studies have shown that precipitation events are influenced by the timing, positioning, and duration of vertically integrated water vapor transport (e.g., atmospheric rivers; Gimeno et al, 2014). Its convergence is crucial for the development of events of intense convective activity (e.g, Ejigu et al, 2021). The vertically integrated moisture fluxes (VIMF) (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Various studies have shown that precipitation events are influenced by the timing, positioning, and duration of vertically integrated water vapor transport (e.g., atmospheric rivers; Gimeno et al, 2014). Its convergence is crucial for the development of events of intense convective activity (e.g, Ejigu et al, 2021). The vertically integrated moisture fluxes (VIMF) (Eq.…”
Section: Methodsmentioning
confidence: 99%
“…The use of GPS/GNSS data in meteorology, hereafter called GPS meteorology, has been introduced. Many applications of GPS meteorology, such as tracking hurricanes/cyclones [3], observing water vapor during a typhoon [4], meteorology forecasting [5], [6], [7]. In this research, we use twenty-three GPS stations from Indonesian Continuously Operating Stations (Ina-CORS) located in East Java to study the spatio-temporal variation of water vapor during 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [2] apply the numerical method to FS prediction; Li et al [3] apply grey theory to FS prediction; Li et al [4,5] put forward several methods to calculate the settlement of sand drain foundation. e results show that the settlement of sand drain foundation caused by lateral deformation must be paid attention to.…”
Section: Introductionmentioning
confidence: 99%